Efektivitas Program Keluarga Berencana (KB) Vasektomi dalam Mengendalikan Angka Kelahiran di Kota Prabumulih - Widodo, Widodo; Maulana, Maulana; Suhaimi, Else (Mahesa Research Center, 2023)
This study aims to describe and analyze the effectiveness of the family planning program in controlling the birth rate in Prabumulih City, as well as the factors that influence it. The research method uses descriptive qualitative, with data collection techniques using: interviews, observation and documentation.The results of this study showed that (1) the Vasectomy program was quite effective in controlling the birth rate in Prabumulih City. This can be seen from efforts to increase awareness and community participation through maturing the age of marriage, birth control, fostering family resilience, and increasing family welfare to create a small, happy, and prosperous family. (2) Supporting factors: organizational characteristics are strengthened through communication strategies, counseling of family planning programs for the community is carried out in a planned manner, with a schedule that has been prepared, while the inhibiting factors are: environmental characteristics in the form of community perceptions, this can be seen from community acceptance of the vasectomy family planning program varies, where some accept and some reject.